Maitrise de la fermentation alcoolique sous stress éthanolique, thermique et osmotique de la souche Saccharomyces cerevisiae YS-DN1 en vue de la préparation du vinaigre de fruits - Majid MOUNIR; Malika BELGRIRE; Safaa LAHNAOUI; Allal HAMOUDA; Philippe THONART; Frank DELVIGNE; Mustapha ISMAILI ALAOUI (Revue Marocaine des Sciences Agronomiques et Vétérinaires, 2016)
The purpose of the present study is to isolate, identify and characterize new yeast species of industrial interest. A total of 54 strains were isolated and identified from agricultural raw products and from by-products of the food industry. Among these, four strains were selected, purified and tested for their ability to perform efficient fermentation on Bouslikhène date juice. After the sequencing of the 18S gene of the ribosomal DNA, the two strains YS-DN1 and YS-M isolated respectively from dates and molasses have been identified belonging to Saccharomyces cerevisiae species. In addition, the other two strains, YS-OMP and YS-G isolated from olives and grapes belonged to Kluyveromyces marxianus (78% homology) and Candida utilis (89% homology) species, respectively. In addition, YS-DN1 strain showed the highest performance in terms of ethanol production in comparison with two other industrial reference strains. YS-DN1 strain was the only one that was able to grow at a temperature ranged from 35 to 40°C in the presence of a high alcoholic concentration and aggressive osmotic pressure condition. Finally, production of the cellular biomass of YS-DN1 strain was improved by optimization of temperature, Brix and pH fixed respectively at 29.75°C, 15.7% and 4.15. These values allowed to obtain a maximum of cells of about 8.4x10 8 UFC/ml. It was concluded that this strain is well suited for fruit vinegar production at a large-scale.